Sensory and motor cortical excitability changes induced by rTMS and sensory stimulation in stroke: A randomized clinical trial - de Freitas Zanona, Aristela; Romeiro da Silva, Andressa Claudia; Baltar do Rego Maciel, Adriana; Shirahige Gomes do Nascimento, Livia; Bezerra da Silva, Amanda; Piscitelli, Daniele; Monte-Silva, Katia (Frontiers in Neuroscience, 2023)
Background: The ability to produce coordinated movement is dependent on dynamic interactions through transcallosal fibers between the two cerebral hemispheres of the brain. Although typically unilateral, stroke induces changes in functional and effective connectivity across hemispheres, which are related to sensorimotor impairment and stroke recovery. Previous studies have focused almost exclusively on interhemispheric interactions in M1. Objective: To identify the presence of interhemispheric asymmetry (ASY) of somatosensory cortex (S1) excitability and to investigate whether S1 repetitive transcranial magnetic stimulation (rTMS) combined with sensory stimulation (SS) changes excitability in S1 and the motor cortex (M1), as well as S1 ASY, in individuals with subacute stroke. Methods: A randomized Clinical Trial. Participants with a single episode of stroke, in the subacute phase, between 35 and 75 years old, were allocated, randomly and equally balanced, to four groups: rTMS/sham SS, sham rTMS/SS, rTMS/SS, and sham rTMS/Sham SS. Participants underwent 10 sessions of S1 rTMS of the lesioned hemisphere (10 Hz, 1500 pulses) followed by SS. SS was applied to the paretic upper limb (UL) (active SS) or non-paretic UL (sham SS). TMS-induced motor evoked potentials (MEPs) of the paretic UL and somatosensory evoked potential (SSEP) of both ULs assessed M1 and S1 cortical excitability, respectively. The S1 ASY index was measured before and after intervention. Evaluator, participants and the statistician were blinded. Results: Thirty-six participants divided equally into groups (nine participants per group). Seven patients were excluded from MEP analysis because of failure to produce consistent MEP. One participant was excluded in the SSEP analysis because no SSEP was detected. All somatosensory stimulation groups had decreased S1 ASY except for the sham rTMS/Sham SS group. When compared with baseline, M1 excitability increased only in the rTMS/SS group. Conclusion: S1 rTMS and SS alone or in combination changed S1 excitability and decreased ASY, but it was only their combination that increased M1 excitability. Clinical Trials (NCT03329807)